Instagram as CSR bridge: Comparing hotel strategies in Indonesia-France - Widiantara, I Made; Bonneau, Marie Christine; Putra, Kadek Dwi Cahaya; Arsawan, I Wayan Edi; Saputra, Upayana Wiguna Eka (Jurnal Kajian Komunikasi, 2025)
Background: This study compares the practice of CSR communication by French hotels operating in Jakarta (Indonesia) and Paris (France). It explores what CSR themes the hotels communicate and which of them lead to consumer engagement in the form of likes, comments, and shares. Purpose: The purpose of this study is to investigate the CSR communication strategies of French hotels operating in Jakarta and Paris and determine the relationship between CSR communication and consumer engagement. Methods: The samples, seven (7) Accor hotels operating in Jakarta and six (6) Accor hotels operating in Paris, were purposively selected. The content analysis method was used, and data were collected from the hotels’ Instagram accounts. The data were then examined using descriptive statistical analysis and multiple regression techniques. Results: The data analysis shows differences in the CSR communication strategy applied by the two sampled hotels. Both French hotels in Jakarta and Paris use Instagram to publish information about their CSR programs, but French hotels in Jakarta publish more CSR posts on Instagram than those in Paris. French hotels in Jakarta focus on environment, society, and economic prosperity, while French hotels in Paris focus on environment, diversity, and society. Customers of French hotels in Jakarta show more engagement, particularly through likes and comments, compared to those in Paris, where engagement is limited to likes. Neither group showed engagement in the form of shares. Implications: Hotels should be more selective in communicating CSR via Instagram, considering the CSR themes that customers care about. It could help improve customer engagement and create a more effective CSR communication strategy.